4D spiral imaging of flows in stenotic phantoms and subjects with aortic stenosis. Issue 3 (27th April 2015) - Negahdar, MJ; Kadbi, Mo; Kendrick, Michael; Stoddard, Marcus F.; Amini, Amir A.
Abstract : Purpose: The utility of four‐dimensional (4D) spiral flow in imaging of stenotic flows in both phantoms and human subjects with aortic stenosis is investigated. Methods: The method performs 4D flow acquisitions through a stack of interleaved spiral k‐space readouts. Relative to conventional 4D flow, which performs Cartesian readout, the method has reduced echo time. Thus, reduced flow artifacts are observed when imaging high‐speed stenotic flows. Four‐dimensional spiral flow also provides significant savings in scan times relative to conventional 4D flow. Results: In vitro experiments were performed under both steady and pulsatile flows in a phantom model of severe stenosis (one inch diameter at the inlet, with 87% area reduction at the throat of the stenosis) while imaging a 6‐cm axial extent of the phantom, which included the Gaussian‐shaped stenotic narrowing. In all cases, gradient strength and slew rate for standard clinical acquisitions, and identical field of view and resolution were used. For low steady flow rates, quantitative and qualitative results showed a similar level of accuracy between 4D spiral flow (echo time [TE] = 2 ms, scan time = 40 s) and conventional 4D flow (TE = 3.6 ms, scan time = 1:01 min). However, in the case of high steady flow rates, 4D spiral flow (TE = 1.57 ms, scan time = 38 s) showed better visualization and accuracy as compared to conventional 4D flow (TE = 3.2 ms, scan time = 51 s). At low pulsatile flow rates, a good agreement was observed between 4D spiral flow (TE = 2 ms, scan time = 10:26 min) and conventional 4D flow (TE = 3.6 ms, scan time = 14:20 min). However, in the case of high flow‐rate pulsatile flows, 4D spiral flow (TE = 1.57 ms, scan time = 10:26 min) demonstrated better visualization as compared to conventional 4D flow (TE = 3.2 ms, scan time = 14:20 min). The feasibility of 4D spiral flow was also investigated in five normal volunteers and four subjects with mild‐to‐moderate aortic stenosis. The approach achieved TE = 1.68 ms and scan time = 3:44 min. The conventional sequence achieved TE = 2.9 ms and scan time = 5:23 min. In subjects with aortic stenosis, we also compared both MRI methods with Doppler ultrasound (US) in the measurement of peak velocity, time to peak systolic velocity, and eject time. Bland‐Altman analysis revealed that, when comparing peak velocities, the discrepancy between Doppler US and 4D spiral flow was significantly less than the discrepancy between Doppler and 4D Cartesian flow (2.75 cm/s vs. 10.25 cm/s), whereas the two MR methods were comparable (−5.75 s vs. −6 s) for time to peak. However, for the estimation of eject time, relative to Doppler US, the discrepancy for 4D conventional flow was smaller than that of 4D spiral flow (−16.25 s vs. −20 s). Conclusion: Relative to conventional 4D flow, 4D spiral flow achieves substantial reductions in both the TE and scan times; therefore, utility for it should be sought in a variety of in vivo and complex flow imaging applications. Magn Reson Med 75:1018–1029, 2016. © 2015 Wiley Periodicals, Inc.